Different Uses for Remote Labs in Electrical Engineering Education: Initial Conclusions of an Ongoing Experience - Pavani, Ana (2018)
Laboratories are a fundamental part of engineering education due to the very nature of the engineering profession. This is a characteristic of all engineering courses, though it may vary from one curriculum to the other and even in the same curriculum. This paper is dedicated to the analysis of different applications of a remote lab in an Electrical Engineering curriculum. If the types of experiments it offers are concerned, it is classified as an Electric and Electronic Circuits lab; one in a set that also has Digital Electronics, Analog Electronics, Electrical Machines, Control Systems, etc. But it is not a traditional lab – it is a remote lab, with traditional components remotely accessed over the Internet. This work presents the preliminary results of the deployment of VISIR – a remote lab for Electric and Electronic Circuits in some courses. It discusses the different course contexts and how the use of VISIR was adapted to each one. Results of students’ opinions are presented and discussed.